Frequency of factors that complicate the identification of mild traumatic brain injury in level I trauma center patients. (March 2016) - Furger, Robyn E; Nelson, Lindsay D; Lerner, E Brooke; McCrea, Michael A
Aim: Determine the frequency of factors that complicate identification of mild traumatic brain injury (mTBI) in emergency department patients.Setting: Chart review.Materials & methods: Records of 3042 patients (age 18–45 years) exposed to a potential mechanism of mTBI were reviewed for five common complicating factors and signs of mTBI.Results: Most patients (65.1%) had at least one complicating factor: given narcotics in the emergency department (43.7%), on psychotropic medication (18.4%), psychiatric diagnosis (15.3%), alcohol consumption near time of admission (14.2%) and preadmission narcotic prescription (8.9%).Conclusion: Our findings highlight the frequency of these confounding factors in this population. Future research should identify how these factors interact with performance on assessment measures to improve evidence-based mTBI assessment in this population.